Echocardiographic prediction of surgical reparability in degenerative mitral regurgitation due to leaflet prolapse: a review. (2nd September 2019) - Mantovani, Francesca; Bursi, Francesca; Di Giannuario, Giovanna; Barbieri, Andrea
ABSTRACT: Introduction : Despite current guidelines provide recommendations for the optimal management of degenerative mitral regurgitation (MR), this condition remains often undertreated with delay in surgical referral and dismal effect on outcomes. Areas covered : This review focuses on the role of echocardiography in guiding mitral valve (MV) surgical repair in degenerative MR due to leaflet prolapse. Expert opinion : A stepwise protocol-driven echocardiography shared by referring physician and surgeon may help to guide referral to surgical repair in degenerative MR. This protocol particularly is useful to identify the ideal patho-anatomy for a successful and durable repair especially when early surgery is proposed and to refer the patient to centers of excellence in case of complex anatomy. Nearly 100% repair rate can be achieved when the surgical technique is adapted to the lesions seen in each valve. Three-dimensional echocardiography predicts repair complexity may be useful and should therefore be implemented. However, the current literature is far from comprehensive deriving from small, single-center studies. Therefore, reproducibility and external validation, especially with newly developed quantitative automated software, are still needed.